Escherichia Coli O157:H7 risk assessment for production and cooking of restructured beef steaks - M.T. Ortega-Valenzuela; H. Thippareddi; Randall K. Phebus; James L. Marsden; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2001)
Distribution of Escherichia coli O157:H7 in restructured beef from artificially inoculated meat pieces and destruction of E. coli O157:H7 in restructured beef steaks prepared from artificially inoculated meat was evaluated following broiling and grilling. In Study I, longissimus dorsi trimmings were inoculated with fluorescently marked E. coli O157:H7 cells to microscopically identify bacterial distribution throughout restructured steak cross-sections. E. coli O157:H7 fluorescent density was observed along the glue lines where meat pieces were enzymatically attached. Study II quantified the level of E. coli O157:H7 throughout the entire thickness of restructured beef. Cross-sectional slices of core samples from the steaks showed that bacterial contamination was evenly distributed (ca. 106 CFU/g). Study III determined the extent of E. coli O157:H7 reduction achieved during cooking. Beef trimmings were inoculated to a level of 107 CFU/g and used to prepare restructured beef chubs. Restructured steaks of three thicknesses (0.5, 1.0, and 1.5 inches) were sliced from the chubs and cooked to one of six target internal temperatures (120, 130, 140, 150, 160, or 170°F) by commercial gas grill or oven broiler. Broiling was more effective than grilling, although E. coli O157:H7 survival decreased as endpoint temperatures increased incrementally. To achieve an adequate level of safety confidence, restructured steaks should be cooked in a manner similar to ground beef; to an internal temperature of at least 160°F.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; E. coli O157:H7; Restructured beef steaks; Cooking